POSSIBILITIES OF EDUCATIONAL GAME DICTIONARIES IN REPRESENTATION OF PHRASEOLOGY TO YOUNGER SCHOOLCHILDREN - Rogaleva, Elena; Nikitina, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article summarizes domestic and foreign experience of creating textbooks in а game format and presents an innovative concept of educational gamificated phraseographic text intended for the younger schoolchildren. The goals and objectives of the game dictionary projects of the Experimental laboratory of educational lexicography of Pskov state University are determined. The macrostructure and parametric model of educational gamificated dictionaries are presented. The lexicographical game techniques of etymologization of phraseological units are described. The results of the training experiment conducted in schools of Pskov on the materials of the author's dictionaries are also presented. They confirm the effectiveness of the developed methodology of gamificated lexicographical representation of phraseology and the practical value of dictionaries.